ANALISIS PROSES PEMBELAJARAN MATEMATIKA DENGAN MENGIMPLEMENTASIKAN K13 DI MTS SWASTA AL WASHLIYAH BANGUN PURBA - Fadzillah Agustina Lubis; Hizmi Wardani (Universitas Muhammadiyah Metro, 2024)
In the 2013 curriculum, the learning process is more emphasized using a scientific approach. The scientific approach is learning that encourages children to perform scientific skills, namely: observing, asking questions, collecting information, associating, and communicating. This study aims to determine the learning process of mathematics by implementing the curriculum 2013 in MTs Al Washliyah Bangun Purba. The subjects of this study were 1 Mathematics teacher, and 1 student representative from Class VII and Class VIII. Data collected in the form of observation of the implementation of learning, interviews of teachers and students. Based on the results obtained from the analysis of the learning process of mathematics by implementing the curriculum in 2013 in Mts Al Washliyah Bangun Purba is based on descriptive data and the percentage of RPP observations above obtained a percentage of 80,8% with the assessment criteria of “good”. And based on descriptive data and the percentage of learning implementation above in Class VII obtained a percentage of 85.5% with the assessment criteria of “good” and Class VIII obtained a percentage of 82.5% with the assessment criteria of “good”.